2019
DOI: 10.3390/nu11050948
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Obesity and Preconceptional Weight Loss on Male and Female Offspring Metabolism and Olfactory Performance in Mice

Abstract: According to the “developmental origins of health and disease” (DOHaD) concept, maternal obesity predisposes the offspring to non-communicable diseases in adulthood. While a preconceptional weight loss (WL) is recommended for obese women, its benefits on the offspring have been poorly addressed. We evaluated whether preconceptional WL was able to reverse the adverse effects of maternal obesity in a mouse model, exhibiting a modification of foetal growth and of the expression of genes encoding epigenetic modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
1
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 78 publications
2
23
1
11
Order By: Relevance
“…These results suggest that the male offspring of GD rats are more susceptible to disturbances in body weight, when they are exposed to a high maternal blood glucose level during the middle stage of pregnancy. In this regard, sexual differences in the offspring body weight have been reported in relation to maternal obesity and a maternal high-fat diet model [38,39], where it was shown that the body weight of female offspring did not change.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the male offspring of GD rats are more susceptible to disturbances in body weight, when they are exposed to a high maternal blood glucose level during the middle stage of pregnancy. In this regard, sexual differences in the offspring body weight have been reported in relation to maternal obesity and a maternal high-fat diet model [38,39], where it was shown that the body weight of female offspring did not change.…”
Section: Discussionmentioning
confidence: 99%
“…The animal model, which received the approval (visa 12/062) of the COMETHEA ethical committee (Comité d'éthique pour l'expérimentation animale), registered with the Comité National de Réflexion Ethique sur l'Expérimentation Animale under the n • 45, in accordance with European Union (Directive 2010/63/EU, 22 September 2010) legislation and the National Charter on the Ethics of Animal Experimentation, has been described elsewhere [21,24]. Briefly, as described in Figure 1, half of the C57BL/6J offspring mice born to control (CTRL), obese (OB) or weight-loss (WL) mothers were fed a control (CD: 20% kcal from proteins, 70% from carbohydrates and 10% from fat; #D12450K, Research Diets, New Brunswick, NJ, USA), and half were fed a high-fat diet (HFD: 20% proteins, 20% carbohydrates and 60% fat; #D12492).…”
Section: Sample Processing and Preparationmentioning
confidence: 99%
“…Full details of diet composition are described in [21]. of Animal Experimentation, has been described elsewhere [21,24]. Briefly, as described in Figure 1, half of the C57BL/6J offspring mice born to control (CTRL), obese (OB) or weight-loss (WL) mothers were fed a control (CD: 20% kcal from proteins, 70% from carbohydrates and 10% from fat; #D12450K, Research Diets, New Brunswick, NJ, USA), and half were fed a high-fat diet (HFD: 20% proteins, 20% carbohydrates and 60% fat; #D12492).…”
Section: Sample Processing and Preparationmentioning
confidence: 99%
See 2 more Smart Citations